4+6c+13=7c-5-c

Simple and best practice solution for 4+6c+13=7c-5-c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+6c+13=7c-5-c equation:


Simplifying
4 + 6c + 13 = 7c + -5 + -1c

Reorder the terms:
4 + 13 + 6c = 7c + -5 + -1c

Combine like terms: 4 + 13 = 17
17 + 6c = 7c + -5 + -1c

Reorder the terms:
17 + 6c = -5 + 7c + -1c

Combine like terms: 7c + -1c = 6c
17 + 6c = -5 + 6c

Add '-6c' to each side of the equation.
17 + 6c + -6c = -5 + 6c + -6c

Combine like terms: 6c + -6c = 0
17 + 0 = -5 + 6c + -6c
17 = -5 + 6c + -6c

Combine like terms: 6c + -6c = 0
17 = -5 + 0
17 = -5

Solving
17 = -5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9s+12=9s+27 | | 6x-18x^2=0 | | y=6x-18x^2 | | 4+68+13=7c-5-c | | 4b+12=35 | | 3a+2.1+4a=-0.7 | | G+(-5)=4 | | c*3= | | a+8=75 | | 5x^2=6-12x | | 3c=21 | | 4a-7+(7-3a)= | | 5-(-66)= | | 12x-9=8x-70 | | 4a+2a= | | 12+a-5+2a=4-a+3+4a | | 3x+4y-22=0 | | 4a+2a^2= | | 4a+3= | | 7p-2(3-4p)=12p-(p+4) | | -(5y+4)-(4y-5)=-5 | | p^2=.960 | | 2a(a+2)-4a+3= | | 3(20-12t)=1.1428571(14+21t)-12t | | 5y-15x=40 | | (x-8)(2x+5)=0 | | y=4x^3-2x^2-2x | | 16k=-9 | | 2w-40=16 | | -6.2x=-9.92 | | 4(2x-3)+2x=54 | | -4n-8=3n-12 |

Equations solver categories